Investigating teachers' enactment of engineering design practices in a CAD simulation‐enhanced learning environment. Issue 6 (24th February 2021) - Dasgupta, Chandan; Magana, Alejandra J.; Kirkham, Lisa
Abstract: Engineering design problems are ill‐structured, and as a result, learners find it challenging to engage productively in relevant practices of analysis, synthesis, and evaluation for solving problems in the domain. Teachers find it particularly difficult to effectively support such engagement. Thus, there is a need to understand how teachers orchestrate their classrooms for maximizing opportunities for students to engage in these practices. In this paper, we use the case study methodology to investigate how teachers materialize and enact engineering design practices in a CAD simulation‐enhanced learning environment. Three teachers (cases) provide evidence for the following orchestration techniques—scaffolding development of students' expertise via teacher‐guided decomposition of problem space, apriori teacher‐led parameter determination, and student‐generated contrasting cases. These techniques scaffolded students' engagement in engineering design practices in all three cases. Common themes across the three cases—problem decomposition, modeling of expert practices, and facilitating students' active involvement—revealed a combination of pedagogical strategies that were interconnected and made evident through the cognitive apprenticeship model. The strategies suggest the integration of types of knowledge and engineering practices required for effective apprenticeships in similar contexts.